Life-sentenced prisoners, crime victims, and the multidialog of parole - Dagan, Netanel (Punishment & society, 2025)
This study examined the dynamics of communication between prisoners sentenced for life (lifers), their victims, and parole boards. Against the backdrop of penal dialogue imagined by penal theorists, we analyzed the narratives of lifers and of their victims during parole hearings in Israel, to explore the construction of a multi-dialogue between prisoners, victims, and parole boards. Our findings reveal that both lifers and victims predominantly framed the crime and its aftermath in personal rather than public terms. Lifers expressed persistent internal anguish, the perceived impossibility of self-forgiveness, and the enduring memory of their victims. Victims emphasized private harm, concerns about the risk that perpetrators still present, and the imperative of commemorating the deceased. We critically assessed whether these narratives challenged or complemented the assumptions of the communicative theory of punishment, which advocates a formal censure-oriented, public-focused penal dialogue culminating in reconciliation. This research investigates possible gaps between communicative ideals and penal realities concerning life imprisonment and uncovers the potential inherent in parole hearings as a communicative penal forum.